The Emotional Modulation of Facial Mimicry: A Kinematic Study - Tramacere, Antonella; Ferrari, Pier F.; Gentilucci, Maurizio; Giuffrida, Valeria; De Marco, Doriana (Frontiers in Psychology, 2018)
It is well established that the observation of emotional facial expression induces facial mimicry responses in the observers. However, how the interaction between emotional and motor components of facial expressions can modulate the motor behaviour of the perceiver is still unknown. We have developed a kinematic experiment to evaluate the effect of different oro-facial expressions on perceiver’s face movements. Participants were asked to perform two movements, i.e., lip stretching and lip protrusion, in response to the observation of four meaningful (i.e., smile, angry-mouth, kiss and spit) and two meaningless mouth gestures. All the stimuli were characterized by different motor patterns (mouth aperture or mouth closure). Response Times and kinematics parameters of the movements (amplitude, duration and mean velocity) were recorded and analyzed. Results evidenced a dissociated effect on reaction times and movement kinematics. We found shorter reaction time when a mouth movement was preceded by the observation of a meaningful and motorically congruent oro-facial gesture, in line with facial mimicry effect. On the contrary, during execution, the perception of smile was associated with the facilitation, in terms of shorter duration and higher velocity of the incongruent movement, i.e., lip protrusion. The same effect resulted in response to kiss and spit that significantly facilitated the execution of lip stretching. We called this phenomenon facial mimicry reversal effect, intended as the overturning of the effect normally observed during facial mimicry. In general, the findings show that both motor features and types of emotional oro-facial gestures (conveying positive or negative valence) affect the kinematics of subsequent mouth movements at different levels: while congruent motor features facilitate a general motor response, motor execution could be speeded by gestures that are motorically incongruent with the observed one. Moreover, valence effect depends on the specific movement required. Results are discussed in relation to the Basic Emotion Theory and embodied cognition framework.